Rituals post Haldi ceremony - Mumbai Archive Project Team (Jio Institute, 2024)
After the conclusion of the haldi (turmeric) ceremony, the bride and groom are washed with water. Earlier in the day, women in the family collect water from a well in several pots. Before using it for this purpose, the water is consecrated through prayers and rituals.